Vallejo and Vanguardia: a troubled relationship - Cornejo Polar, Jorge (1991)
A constant inquiry of Vallejo's critics has been the one about of the changes in this poetry during the years 1918 and 1922, between Los Heraldos Negros and Trilce. Using recent research approaches, the author tries to answer this question in order to make an exhaustive review of the possible explanations and ending with a personal hypothesis. The author also studies the relationship between Trilce and Escalas Melografiadas. In the two books appear the change studied, and a critical analysis can bring new lights to reach a better understanding of the transformation from the first to the second Vallejo.